PENGARUH BELIEF SYSTEM DAN BOUNDARY SYSTEM TERHADAP INTELLECTUAL CAPITALMELALUI IMPLEMENTASI ERP SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG MENERAPKAN SISTEM ERP DI INDONESIA - Shendy Christyanto; Priskila Adiasih; Saarce Elsye Hatane (Business Accounting Review, 2018)
The aim of this study was to identify whether there is influence between the belief system and the boundary system against intellectual capital through the implementation of ERP as intervening variable. The population used in this study is a company in Indonesia that implements ERP system. The sample of this research is 36 companies in Indonesia that have implemented ERP system.     Data analysis techniques used in this research was the partial least square to describe relationships between variables. Data processing using WarpPLS 5.0. The results showed that belief system and boundary system has a positive and significant influence towards intellectual capital through the implementation of ERP as intervening variable on the companies that implement ERP system in Indonesia.